Pengaruh Dukungan Psikososial, KIE dan Fasilitas Layanan Kesehatan terhadap Keputusan Ibu Hamil dalam Memilih ANC dan Persalinan - Fernando Pausoan Gultom, Doddy; Rita Wahidi, Kemala; Nofierni, Nofierni (Green Publisher Indonesia, 2025)
This study aims to analyze the role of Social Media Marketing as a moderation variable on the influence of psychosocial support, health communication, information and education (KIE), and health facilities on pregnant women's decisions in choosing Antenatal Care (ANC) and childbirth services at Petukangan General Hospital. Psychosocial support, which includes emotional and social support from family and health workers, plays an important role in lowering anxiety and improving the comfort of pregnant women. In addition, an effective KIE is able to increase the understanding of mothers-to-be regarding the risks and available health care options. Health facilities at Petukangan Hospital, including medical equipment, hygiene, and comfort of the treatment room, are also important aspects that affect the preferences of pregnant women. This study found that Social Media Marketing has a significant role as a moderation variable. With the right utilization, social media can be an effective platform to disseminate information about the quality of hospital services and facilities, so that it can influence the decision of pregnant women. The results of the analysis showed that the combination of psychosocial support, good information and education, quality health facilities, and effective marketing through social media increased the tendency of pregnant women to choose Petukangan Hospital as the place of delivery. This study underscores the importance of the right social media marketing strategy in improving hospital competitiveness in the digital era. Recommendations are given for Petukangan Hospital to strengthen digital marketing strategies to maximize the positive influence on the decisions of potential patients, especially among pregnant women.